Co-Creative Service Innovation on Social Media: An Empirical Study in an International Coffee Cafe Chain in Indonesia - Siti Rahayu; Eva Emilia Tan; Adi Prasetyo Tedjakusuma (Journal of Entrepreneurship and Business, 2023)
Purpose: This study aims to determine and analyze the effect of consumer innovativeness and attitude toward CCSI on social media, subjective norms, and perceived behavior control on intention to co-create and adoption intention. The object of this study is an international coffee café chain in Indonesia. Method: This study uses primary data sources by distributing questionnaires online. There are 150 questionnaires used in the data processing. Research data was processed using SEM (Structural Equation Modeling) with IBM SPSS Statistic software and AMOS 22. Result: The results show that 6 hypotheses are supported and 1 hypothesis is not supported. Consumer innovativeness, subjective norms, and perceived behavior control affect the intention to co-create. Consumer innovativeness, perceived behavioral control, and intention to co-create affect adoption intention. Hypothesis 3: the effect of attitude toward CCSI on social media on intention to co-create is not supported.